2021
DOI: 10.52080/rvgluz.26.e6.11
|View full text |Cite
|
Sign up to set email alerts
|

Ideas de negocio para reactivar el turismo en pandemia en “La Encantada”, Chulucanas, Perú

Abstract: La pandemia causada por el COVID-19 paralizó el sector turístico y afectó negativamente el empleo a los artesanos dedicados al comercio de la cerámica. El objetivo de este estudio es identificar las ideas de negocio de los artesanos de “La Encantada”, Chulucanas, Perú en esta época caracterizada por realidades pandémicas. Se realizó una investigación acción con 12 artesanos dedicados a la cerámica en “La Encantada” a los cuales se les practicó una entrevista y se utilizó el método de filtro macro y micro para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…La gestión de la señalización involucra el consenso de los actores locales para priorizar la implementación de la señalización de los atractivos turísticos y fortalecer la identidad cultural del territorio local, valorando la historia de la comunidad anfitriona local (Moreno-Quispe et al, 2021). El museo de sitio y zona arqueológica de Narihuala representa el legado de la cultura Tallan, que aún mantiene viva la "técnica de pateleo" que permite a los emprendedores de cerámicas, producir y comercializar artesanías monocromas y con productos locales conservando una práctica prehispánica.…”
Section: Revista De Cienciasunclassified
“…To reactivate tourism, it is necessary to conceive innovative ideas and business plans that can meet current needs [2]. Among these are strategies related to ecotourism, also known as landscape tourism or ecological tourism, which focuses on offering tourist activities in natural environments while preserving the environment.…”
Section: Introductionmentioning
confidence: 99%